Evaluasi Aplikasi DOI by RJI pada Aspek Usability dan User Experiance Menggunakan Metode System Usability Scale (SUS) dan User Experience Questionnaire (UEQ) - Maulana, Asep Erlan (Explorer, 2024)
Indonesian Journal Volunteers have an application that makes it easy for journal managers to become members of Crossref and subscribe to Digital Object Identifiers (DOI). One of the services that RJI currently has is the DOI application. The purpose of this study was to test the quality of usability and to evaluate the level of user experience satisfaction from the DOI by RJI application. There are 2 methods used in this research. The first method of the System Usability Scale (SUS) is used to measure usability aspects. While the second method of the User Experience Questionnaire (UEQ) is used to produce evaluation results of user satisfaction levels from the user experience. From 23 respondents there are results of user satisfaction levels with a score of 65 with category D and can be said to be well received by users. Aspects of the level of satisfaction there is a positive level results with the highest mean value on the efficiency scale (Efficiency) which is 1.554 followed by the stimulation scale (Stimulation) with a value of 1.511. Then the value of the attractiveness scale is 1.493, the dependability scale is 1.478, the novelty scale is 1.326 and the Perspicuity scale is 1.272. This shows that the level of user satisfaction in using the DOI by RJI application has a positive user experience. Because all levels of the scale are higher than the standard value of 0.8.